Effect of the performance of physical and non-physical facilities on higher institutional facilities - Abdullahi, Isa; Wan Yusof, Wan Zahari (Emerald Publishing Limited, 2018)
The role of institutional facilities is of paramount importance to ensure quality of teaching and learning with respect to achieving quality of education in any given higher educational institutions (HEIs). The purpose of this paper is to determine the performance of physical and non-physical facilities of higher institutional facilities.